2019
DOI: 10.1017/s1355771819000311
|View full text |Cite
|
Sign up to set email alerts
|

Introducing New Audiences to Sound-Based Music through Creative Engagement

Abstract: This article will outline the experience of researchers at De Montfort University (DMU) (Leicester, UK) in devising and delivering workshops on sound-based creativity (sbc). These workshops supported and guided participants through the process of listening training, recording and composing their own sound-based pieces. As well as engaging participants in sound-based composition, the aim of these workshops was to introduce them to examples from the repertoire of sbm. The final workshops involved the collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Valenzuela and Codina (2014) showed primary school children who had prior musical knowledge demonstrated a higher engagement and motivation in their music lessons. Contrastingly, Holland (2016) showed that with sbm , while children with prior musical training might use different strategies to compose music, both groups (with and without prior musical training) showed similar levels of engagement.…”
Section: The Pedagogic Potential Of Sound-based Musicmentioning
confidence: 96%
See 3 more Smart Citations
“…Valenzuela and Codina (2014) showed primary school children who had prior musical knowledge demonstrated a higher engagement and motivation in their music lessons. Contrastingly, Holland (2016) showed that with sbm , while children with prior musical training might use different strategies to compose music, both groups (with and without prior musical training) showed similar levels of engagement.…”
Section: The Pedagogic Potential Of Sound-based Musicmentioning
confidence: 96%
“…Alongside Wolf’s (2013a) doctoral research, Therapontos’s (2013) thesis investigated the implementation of sbm in schools in Cyprus, stating that sbm provided an inclusive education. Further developments from Holland (2016) found that pupil engagement increased in all classes following his method of heightened listening training.…”
Section: The Pedagogic Potential Of Sound-based Musicmentioning
confidence: 98%
See 2 more Smart Citations
“…Using mean square error and signal-to-noise ratio to judge, it is found that DB4 is the best of 10 wavelet packet basis, so DB4 in Daubechies series is selected as the wavelet packet basis, and the number of decomposes layers in the wavelet packet decomposition of suppressing music noise is set as 3. For a given signal F(x), its orthogonal wavelet decomposition formula is as follows [34]:…”
Section: Music Noise Reductionmentioning
confidence: 99%